ETIKA PROFESI PENGAWAS PENDIDIKAN DALAM PERSPEKTIF ISLAM - hazrullah hazrullah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The idea of the education supervisor profession ethics code departs from the reality of some existing education supervisors who ignore the values of morality and lack of a strong awareness to heed professional ethics when providing professional expert services to teachers even though the professional actors already have a professional code of ethics as the moral standard. One solution for teachers to remain professional in teaching is by upholding ethics, professionalism, and discipline. The code of ethics of the supervisory profession in principle contains moral values that underlie professional personality, namely responsibility, justice, autonomy, and moral integrity. Professional supervisor ethics cannot be separated from Islamic ethical values on the basis of understanding of the Qur'an and Hadith, so basically, the code of ethics of the education supervisor profession should be in line with the Islamic values.